MARKETING STRATEGY OF TELANG FLOWER HERBAL TEA (Clitoria ternatea) (CASE STUDY IN CLITEA HOUSEHOLD INDUSTRY) - M.A.T., Pero; Putri, B. R. T.; Suarta, G. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aims to analyze internal and external factors that affect the marketing strategy of Clitea, analyze Clitea's business position in the herbal tea industry, and recommend the right marketing strategy for Clitea products. This research is a case study conducted at Clitea home industry in North Kuta, Badung. This research was conducted in March-May 2022. The study used 80 respondents, consisting of 75 consumer respondents, 2 academic respondents, 1 practitioner respondent, and 2 policy makers (government) respondents. Sources of data used, namely primary data and secondary data. Data were collected through observation, in-depth interviews, interviews with questionnaires, and related literature searches. The analysis used in this study, namely 1) IFE and EFE analysis; 2) IE analysis; 3) SWOT analysis; and 4) QSPM analysis. The results of the IFE and EFE analysis of this study indicate that Clitea's business position in the herbal tea industry is in cell II of IE matrix, namely the division of grow and build with intensive strategies market penetration, market development, and product development. Based on the results of SWOT and QSPM analysis, the priority strategy in Clitea's marketing is create economic priceing strategy to attract customers, increasing sales and product popularity with a TAS value of 2.37.